Comparison of Five Bacteriophages as Models for Viral Aerosol Studies - Turgeon, Nathalie (American Society for Microbiology, 2014)
Bacteriophages are perceived to be good models for the study of airborne viruses because they are safe to use, some of them display structural features similar to those of human and animal viruses, and they are relatively easy to produce in large quantities. Yet, only a few studies have investigated them as models. It has previously been demonstrated that aerosolization, environmental conditions, and sampling conditions affect viral infectivity, but viral infectivity is virus dependent. Thus, several virus models are likely needed to study their general behavior in aerosols. The aim of this study was to compare the effects of aerosolization and sampling on the infectivity of five tail-less bacteriophages and two pathogenic viruses: MS2 (a single-stranded RNA [ssRNA] phage of the Leviviridae family), Φ6 (a segmented double-stranded RNA [dsRNA] phage of the Cystoviridae family), ΦX174 (a single-stranded DNA [ssDNA] phage of the Microviridae family), PM2 (a double-stranded DNA [dsDNA] phage of the Corticoviridae family), PR772 (a dsDNA phage of the Tectiviridae family), human influenza A virus H1N1 (an ssRNA virus of the Orthomyxoviridae family), and the poultry virus Newcastle disease virus (NDV; an ssRNA virus of the Paramyxoviridae family). Three nebulizers and two nebulization salt buffers (with or without organic fluid) were tested, as were two aerosol sampling devices, a liquid cyclone (SKC BioSampler) and a dry cyclone (National Institute for Occupational Safety and Health two-stage cyclone bioaerosol sampler). The presence of viruses in collected air samples was detected by culture and quantitative PCR (qPCR). Our results showed that these selected five phages behave differently when aerosolized and sampled. RNA phage MS2 and ssDNA phage ΦX174 were the most resistant to aerosolization and sampling. The presence of organic fluid in the nebulization buffer protected phages PR772 and Φ6 throughout the aerosolization and sampling with dry cyclones. In this experimental setup, the behavior of the influenza virus resembled that of phages PR772 and Φ6, while the behavior of NDV was closer to that of phages MS2 and ΦX174. These results provide critical information for the selection of appropriate phage models to mimic the behavior of specific human and animal viruses in aerosols.